2021
DOI: 10.31219/osf.io/paby6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid elicitation and quantile-parametrized likelihood

Abstract: This paper extends the application of indirect Bayesian inference to probability distributions defined in terms of quantiles of the observable quantities. Quantile-parameterized distributions are characterized by high shape flexibility and interpretability of its parameters, and are therefore useful for elicitation on observables. To encode uncertainty in the quantiles elicited from experts, we propose a Bayesian model based on the metalog distribution and a version of the Dirichlet prior. The resulting “hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Through experimentation involving 103 judges, Abbas et al (2008) showed "slight but consistent superiority" for the variable interval method along several dimensions such as accuracy and precision of the estimated fractiles. It is also possible to jointly ask both quantiles and probability, a quantile-probability tuple (Perepolkin et al, 2021), in which case the method is referred to as PV-method (Spetzler and Holstein, 1975).…”
Section: Univariate Priormentioning
confidence: 99%
See 2 more Smart Citations
“…Through experimentation involving 103 judges, Abbas et al (2008) showed "slight but consistent superiority" for the variable interval method along several dimensions such as accuracy and precision of the estimated fractiles. It is also possible to jointly ask both quantiles and probability, a quantile-probability tuple (Perepolkin et al, 2021), in which case the method is referred to as PV-method (Spetzler and Holstein, 1975).…”
Section: Univariate Priormentioning
confidence: 99%
“…A challenge in doing elicitation in the observable space is the difficulty to separate two sources of randomness: due to θ and due to y (Garthwaite et al, 2005;Perepolkin et al, 2021). There are some solutions to that, for instance, Kadane and Winkler (1988) proposed to the expert to consider only the mean ȳ, and then conduct other assessment tasks to elicit the randomness in y.…”
Section: Elicitation In Observable Spacementioning
confidence: 99%
See 1 more Smart Citation
“…This direct approach requires no translation. For example, the Bayesian quantile-parameterised likelihood (Hadlock, 2017;Keelin and Powley, 2011) approach of Perepolkin et al (2021) involves updating directly elicited properties of a phenomena, it is unsurprising that such information is associable with many prior distributions.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the primary utility of QPDs lies in their ability to simplify the specification of probability distributions for model parameters, known as prior elicitation (Mikkola et al, 2021). However, these same distributions can also be employed to describe an expert's predictions for the next observation, referred to as predictive elicitation (Winkler, 1980;Kadane, 1980;Akbarov, 2009;Hartmann et al, 2020), or to capture both uncertainty and variability through a two-dimensional probability distribution in hybrid elicitation (Perepolkin et al, 2021a). Through our comprehensive review and identification of research gaps, we aim to contribute to the development of flexible and extensible distributions that can effectively capture expert knowledge.…”
Section: Introductionmentioning
confidence: 99%